PENGGUNAAN KONTRASEPSI DARURAT BAGI KORBAN PEMERKOSAAN UNTUK MENCEGAH KEHAMILAN TIDAK DIINGINKAN (KTD) PERSPEKTIF KEADILAN HAKIKI PEREMPUAN - Fitriani, Elsa Lailatul; Rohmawati, Rohmawati (Departement of Constitutional Law UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
The crime of rape can result in an unwanted pregnancy, which is a significant issue for the victim. This article presents research on regulations for access to emergency contraceptive services and women's absolute justice perspectives on the use of emergency contraception to prevent unwanted pregnancies in cases of rape. This study employs a juridical-normative approach and content analysis to demonstrate that Law Number 12 of 2022 and the Algorithm ic Rules for Health Service Management by the Indonesian Ministry of Health in 2021 have regulated access to emergency contraception. Furthermore, the legality of the use of emergency contraception has been guaranteed in Government Regulation No. 61/2014, article 24, and Minister of Health Regulation No. 21/2021, article 30. The provision of emergency contraception services for victims has successfully reflected the conditions of true justice for women, through efforts to protect women from the risk of unwanted pregnancies and reduce the impact of stigma and violence in the social sphere that often occurs to rape victims.